2014
DOI: 10.1590/s0104-07072014000100014
|View full text |Cite
|
Sign up to set email alerts
|

Representations about suicide of women with history of domestic violence and suicide attempt

Abstract: Suicide attempt is characterized by complex and multifaceted phenomena with significance on global public health. The aim of this study was to grasp the structure of social representations of suicide of women with history of domestic violence and suicide attempt. The study was developed with a qualitative approach, based on the Theory of Social Representations. There were 30 women that responded the Free Word Association Test, all of them with history of domestic violence and suicide attempt by poisoning. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 5 publications
0
8
0
6
Order By: Relevance
“…The psychological illness of the woman, a fact highlighted by the study, is consistent with the findings in the literature. 17,[24][25] A study has shown that the marks on the body of a woman in a situation of gender violence were always accompanied by great moral suffering, exacerbated by her vulnerable condition of victimization. 24 When the attractions and oppositions observed in the utterances of F1+ and F1-were analyzed, we observed that the representations inherent to both groups showed an attraction for the idealization of family, anchored on the vision of family structure and friendship, even though the relatives showed evidence of violence in this space during the interviews.…”
Section: Resultsmentioning
confidence: 99%
“…The psychological illness of the woman, a fact highlighted by the study, is consistent with the findings in the literature. 17,[24][25] A study has shown that the marks on the body of a woman in a situation of gender violence were always accompanied by great moral suffering, exacerbated by her vulnerable condition of victimization. 24 When the attractions and oppositions observed in the utterances of F1+ and F1-were analyzed, we observed that the representations inherent to both groups showed an attraction for the idealization of family, anchored on the vision of family structure and friendship, even though the relatives showed evidence of violence in this space during the interviews.…”
Section: Resultsmentioning
confidence: 99%
“…18 Specifically in the health sector, there are women with physical injuries, caused by direct aggression, to situations of depression and suicidal behavior, resulting from the somatization of their experiences. 6 However, a research carried out with health practitioners reveals that some of them act inadequately, such as: calling the police, stating that the woman is also responsible for the situation, and preparing an expert report. 25 Considering this context, nurses who work in obstetric or emergency care recognize the need for a differentiated approach to the care of women in situations of violence, especially in relation to listening and qualified care.…”
Section: Discussionmentioning
confidence: 99%
“…Women in situations of domestic violence can present several health problems, such as: bruising, headache, gastrointestinal disorders, fatigue, anxiety, decreased libido, post-traumatic stress disorder (PTSD), inappetence, insomnia, low self-esteem, intense sadness, depression, suicidal ideation, and suicide attempt. [6][7] Focusing on alcohol abuse and other drug abuses, researches carried out in Brazil and Canada point out their damages to the health of those involved, such as elevated liver enzymes, steatosis, cirrhosis, insulin resistance, pancreatitis, coagulopathies, frequent falls, aggression, paranoia in daily situations, feelings of loss and humiliation, social isolation, and depression. [8][9] Given the morbimortality of the violence, it is necessary to prepare professionals to recognize women in this situation as early as possible, in order to welcome and direct them to put an end in the abusive relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Pesquisa realizada com mulheres adultas com história de violência doméstica e tentativa de suicídio no município de Salvador (BA) evidenciou que as participantes relacionaram o adoecimento psíquico às agressões cometidas pelo companheiro. 17 Existe elevado percentual de problemas mentais em mulheres que sofreram violência, os quais interferem diretamente na qualidade de vida das vítimas e de suas famílias, podendo resultar em situações de morbidade e perdas potenciais quanto aos aspectos pessoais, sociais, afetivos e econômicos. 9,18 A violência e a depressão geraram graves consequências na vida das participantes, destacando-se o abandono da atividade laboral, a falta de ânimo para realizar as atividades, o isolamento social, o desenvolvimento ou agravo de problemas de saúde e a ausência de expectativas com o futuro.…”
Section: Referênciasunclassified